Foreword - Iwona Zych; Michał Gawlikowski; Joan Oller Guzmán (Polish Archaeology in the Mediterranean, 2020)
Ten years after the Red Sea III conference: "Natural Resources and Cultural Connections of the Red Sea", held at the British Museum on 27–28 October 2006, enough new data has been made available to warrant another in-depth look at the archaeology of natural resources extraction and processing (mines, workshops, etc.). The main themes of the conference are: 1) economic significance of commerce in natural resources passing through the Red Sea; 2) intermediaries in the natural resources trade (“Who dun’it”); 3) other archaeological categories coexistent with the natural resources trade (pottery, glass etc.); 4) language/epigraphy: terms for natural resources: mining and processing/crafts work; 5) ethnoarchaeological evidence for exploitation and processing of natural resources